Secret in the stone - Benko, Kamilla (Benko, Kamilla. Unicorn quest., 2020)
Claire and Sophie journey to Stonehaven where Claire can be trained to use her Gemmer abilities to awaken the unicorns, but Sophie discovers they are in great danger.